Angioplasty and Stenting of Distal Anastomotic Stenosis of Femoropopliteal Bypass Graft Using Helical Interwoven Nitinol Stents - Chan, Yiu Che; Cheng, Stephen (International Journal of Angiology, 2016)
Minimally invasive endovascular options of angioplasty and stenting can be used to treat distal anastomotic stenoses in lower limb bypass grafts, but stents near the knee joint may fracture. The nitinol helical interwoven structure of the Supera stents (IDEV Technologies Inc., Houston, TX) has improved flexibility and kink resistance. We report a patient who received salvage angioplasty and Supera stenting of the distal anastomosis of femoropopliteal bypass grafts with good mid-term results. Considering the high radial strength and fracture resistance, these Supera stents may be a good treatment option in salvaging failing bypass grafts.
Keywords: femoropopliteal bypass grafts; anastomotic stenosis; nitinol helical interwoven Supera stents